Modifikasi algoritma Hill cipher dengan matriks kunci berupa matriks ketetanggaan - Agusfrianto, Fakhry Asad; Ambarwati, Lukita; Mahatma, Yudi (Majalah Ilmiah Matematika dan Statistika, 2023)
Cryptography is one of the parts in mathematics, especially applied mathematics. Cryptography is the science that studies how to secure information that we don't want others to know about the information we have. Based on the development of the times, cryptography is divided into two consisting of classical cryptography and modern cryptography. In this paper, the focus of discussion is on classical cryptography. Furthermore, there are many kinds of classical cryptographic algorithms, such as the Caesar cipher algorithm, the Playfair cipher algorithm, the Vigenere cipher algorithm, and the Hill Cipher algorithm. The focus of discussion in this paper is on the Hill cipher algorithm. The modifications made to the Hill cipher algorithm lie in its key matrix. In this paper, it will be shown how to encrypt and decrypt the message we want to send using the Hill cipher algorithm with the matrix being a adjacency matrix. In which case, the adjacency matrix itself is obtained from the representation of the graph. It is hoped that this algorithm can avoid crypt attacks, especially on ciphertext only-attack.Keywords: Hill cipher algorithm, cryptography, adjacency matrix, plaintext, ciphertextMSC2020: 94A60